1997
DOI: 10.1016/s0954-6111(97)90052-4
|View full text |Cite
|
Sign up to set email alerts
|

Nacystelyn, a novel lysine salt of N-acetylcysteine, to augment cellular antioxidant defence in vitro

Abstract: Nacystelyn (NAL), a recently-developed lysine salt of N-acetylcysteine (NAC), and NAG, both known to have excellent mucolytic capabilities, were tested for their ability to enhance cellular antioxidant defence mechanisms. To accomplish this, both drugs were tested in vitro for their capacity: (1) to inhibit O2- and H2O2 in cell-free assay systems; (2) to reduce O2- and H2O2 released by polymorphonuclear leukocytes (PMN); and (3) for their cellular glutathione (GSH) precursor effect. In comparison with GSH, NAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0
9

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 36 publications
3
66
0
9
Order By: Relevance
“…The mucolytic effect of NAL is about the same as that of Pulmozyme and the effects are synergistic, as determined by an in vitro test of CF mucus transport [95]. In addition, NAL may have the potential to decrease oxidantinduced IL-8 production [93], decrease the oxidative burst from neutrophils, and increase intracellular GSH levels [91].…”
Section: Nacystelynmentioning
confidence: 99%
See 1 more Smart Citation
“…The mucolytic effect of NAL is about the same as that of Pulmozyme and the effects are synergistic, as determined by an in vitro test of CF mucus transport [95]. In addition, NAL may have the potential to decrease oxidantinduced IL-8 production [93], decrease the oxidative burst from neutrophils, and increase intracellular GSH levels [91].…”
Section: Nacystelynmentioning
confidence: 99%
“…Trials are also being conducted using cysteine-rich Nacystelyn (NAL), a mucolytic with antioxidant and anti-inflammatory activity [91][92][93][94]. NAL differs from N-acetylcysteine (Mucomyst), which has a long history of use in CF, by the addition of lysine, raising the pH from 2.2 to 6.0 and increasing the water solubility.…”
Section: Nacystelynmentioning
confidence: 99%
“…The advantage of NAL over NAC is that it has a neutral pH in solution, whereas NAC is acidic. NAL can be aerosolized into the lung without causing significant side-effects [248]. GILLISSEN et al [248] compared the effects of NAL and NAC and found that both drugs enhanced intracellular glutathione levels in alveolar epithelial cells and inhibited H 2 O 2 and O 2 .…”
Section: Immune Effector Responsementioning
confidence: 99%
“…NAL can be aerosolized into the lung without causing significant side-effects [248]. GILLISSEN et al [248] compared the effects of NAL and NAC and found that both drugs enhanced intracellular glutathione levels in alveolar epithelial cells and inhibited H 2 O 2 and O 2 . ± release from human blood-derived polymorphonuclear neutrophils (PMNs) from smokers with COPD.…”
Section: Immune Effector Responsementioning
confidence: 99%
“…Nacystelyn (NAL) is a derivative of N-acetyl-cysteine with an added L-lysine residue, and has been used for treatment of impaired mucociliary clearance and chronic mucus retention in CF patients. 4,5 NAL has been shown to possess antioxidant, 6 mucolytic and anti-inflammatory properties, thus indicating that it may be beneficial for CF patients. 7,8 Clinical trials conducted with NAL in CF patients have demonstrated an improvement in symptoms, with a dose-dependent decrease in sputum viscoelasticity along with a decrease in sputum solids content, and an increase in chloride and sodium concentrations, thus indicating improved mucus clearance.…”
mentioning
confidence: 99%